1981
DOI: 10.1017/s0376892900028150
|View full text |Cite
|
Sign up to set email alerts
|

Gros Morne National Park, Newfoundland, and Parks Canada Policies

Abstract: Gros Morne, one of Canada's newer national parks, covers over 1,900 km2 of exceptionally scenic country on the west coast of Newfoundland. However, the Park was initiated by the provincial government mainly for economic reasons rather than for the value of its natural heritage—particularly to stimulate development in an area of high unemployment. To some degree, this has been achieved—but not without considerable cost, as the area is one of long-established settlement and utilization. Most of the settlements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Gros Morne National Park was established in a region of long-standing settlement and resource use (Crabb, 1981). Thus, it was not surprising that conflicts arose between local residents and park authorities.…”
Section: The Case Of Gros Morne National Parkmentioning
confidence: 99%
See 4 more Smart Citations
“…Gros Morne National Park was established in a region of long-standing settlement and resource use (Crabb, 1981). Thus, it was not surprising that conflicts arose between local residents and park authorities.…”
Section: The Case Of Gros Morne National Parkmentioning
confidence: 99%
“…Thus, it was not surprising that conflicts arose between local residents and park authorities. Crabb (1981) suggested that there were two distinct areas of conflict due to Parks Canada policies: the actual settlements and the traditional semisubsistence use of the land.…”
Section: The Case Of Gros Morne National Parkmentioning
confidence: 99%
See 3 more Smart Citations